BIOINFORMATIC STUDY OF AN ANTITUMOR PROTEIN, AZURIN - Valli S, Abiraami; T, Mythili (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of this study is to analyze the structure and function of an antitumor protein, azurin, thereby giving validation to the protein structure and existing physicochemical properties in the anticancer protein which are responsible for the anticancer activity. Methods: Protein sequence analysis was done using Basic Local Alignment Search Tool (BLAST) with ten different randomly selected species of Pseudomonas obtained from GenBank. The physicochemical properties, prediction of secondary structure, identification of motifs and domains, three-dimensional (3-D) structure of the antitumor protein, validation through Ramachandran plot, multiple sequence alignment (MSA), and phylogenetic analysis were studied and functional property was confirmed through in silico docking. Results: The similarity search (BLAST-P analysis) for the primary sequence from GenBank carried out showed 86% similarity to the second sequence, azurin (Pseudomonas nitroreducens). The ProtParam, ExPASy tool server indicated the presence of essential physicochemical properties in azurin. Secondary structure prediction revealed random coil, extended strand, alpha helix, and beta turn. The study on domains indicated the presence of one domain in azurin responsible for the anticancer activity. The 3-D structural analysis revealed azurin as metalloprotein, of length-128, and polymer-1 with Î±-helices, Î²-sheets, and Î²-barrels. The validation carried out through Ramachandran plot showed the presence of two outliers (phi and psi). The biological relationship between the input sequences was studied through MSA and phylogenetic analysis. Further, azurin docked against the target protein (p53 tumor suppressor) showed the maximum binding affinity confirming its functional property of causing apoptosis. Conclusion: All the properties analyzed in the present study revealed that the azurin protein can act as a very good anticancer agent, and through the phylogenetic analysis, it was identified that Pseudomonas nitroreducens was closely related to the test organism Pseudomonas aeruginosa.